Disclosing Childhoods Research and Knowledge Production for a Critical Childhood Studies - Spyrou, Spyros (Studies in Childhood and Youth, 2018)
Disclosing Childhoods offers a critical account of knowledge production in childhood studies. The book argues for the need to be reflexive about the knowledge practices of the field and to scrutinize the role of researchers in disclosing certain childhoods rather than others. A relational lens is used to critique the ongoing fixation of childhood studies with the unitary child-agent and to re-introduce the question of ontology in knowledge production. The author provides a critical account of childhood studies' trajectory, as well as exploring the key concepts of voice, agency and participation, illustrating the potential of a reflexive stance towards knowledge production. Drawing on poststructuralist and posthumanist thinking, each of these concepts is critiqued for its conceptual limits while productive avenues are offered to reconfigure their utility. Spyrou also addresses the ethics and politics of knowledge production and considers key emerging insights which can contribute towards the development of a more reflexive and critical childhood studies. Students and scholars across a range of disciplines, including childhood studies, anthropology, sociology and geography, will find this book of interest, as well as those interested in qualitative research methodology and social theory. .